TEKNOLOGI PEMBUATAN OBAT HERBAL DAN PAKING SACHET BAGI KELOMPOK DASA WISMA PENGELOLA APOTIK HIDUP DI DESA KLAMPOK KEC. PURWOREJO KLAMPOK, KAB. BANJARNEGARA - Wahju Purbo Juwono; Yuniar Deddy Kurniawan; Nana Supriyana (Universitas Muhammadiyah Semarang, 2017)
Dasawisma in Klampok Village is active in managing live pharmacies, from data of plant species that have beendeveloped has reached 115 types of medicinal plants including turmeric, ginger, and plant for herbal medicinegodok. Utilization of medicinal plants has not been done optimally in utilizing live pharmacies. In the activities ofIbM, the Implementing Team undertakes the application of technology to empower the dasawisma with the trainingof making pasta / wound ointment, godok herbs, and herbal compresses, to produce diabetic herbal healthproducts, herbal medicine for stamina and herbal godog in a dry state. The group is also given the provision to getto know the online marketing with a special WEB for the promotion of the product while for the transaction processwill be directed through apliksi pedia shop online system. WEB development is done by bringing in IT practitionersand online businesses. In the early stages will be sold herbal medicine in the form of dried herbs that are packagedaccording to the type of disease. In the activities of IbM so that the products have unique specifications that aresold are herbal medicine for chronic diseases such as diabetes, high blood and kidney. For packing and gasket isdone gradually for products sold directed to use sachet and higines process with semihetomatic sachets technology,for product which will be marketed to be certified BPPOM and dinkes. Management strengthening is done by a simple team to start to make group management on the management of herbal medicine brewed and godok. bygiving direction and entrepreneurship training, giving information and assistance to get business capital to trainbookkeeping, simple accounting, (cash flow). The training is also done by making semi-automatic sachet higinesSNI standard, training on making and maintaining e-commerce website for selling products, providingentrepreneurship training, bookkeeping training, accounting, product marketing strategy, extension of business andcompany strategy, giving information and assistance to get venture capital. The impact of the increase in income isnot significant because the specific product still needs to be developed further, the sales are still in the raw materialstage, for that in the next stage will be made is a commercial product with diabetes blend, and chronic diseases, theproduct will be in modern gasket with sachet machine economical and semi-automatic. Marketing on the conditionof dry herbs and ointments will be supported by circulation permit.I. Keywords: Herbal Product, Dasawisma. Sachet Machine, Marketing.